Cattle milk and meat network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
This network deals with the humid and sub-humid zones of West and Central Africa. It should facilitate information dissemination but it will also initiate training activities to strengthen national agricultural research activities, plan research...